2008
DOI: 10.1007/s11664-008-0574-5
|View full text |Cite
|
Sign up to set email alerts
|

Electromigration Behavior in Sn-37Pb and Sn-3.0Ag-0.5Cu Flip-Chip Solder Joints under High Current Density

Abstract: The electromigration of conventional Sn-37Pb and Pb-free Sn-3.0Ag-0.5Cu (in wt.%) solder bumps was investigated with a high current density of 2.5 9 10 4 A/cm 2 at 423 K using flip-chip specimens comprised of an upper Si chip and a lower bismaleimide triazine (BT) substrate. Electromigration failure of the Sn-37Pb and Sn-3.0Ag-0.5Cu solder bumps occurred with complete consumption of electroless Ni immersion Au (ENIG) underbump metallization (UBM) and void formation at the cathode side of the solder bump. Finit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…By increasing the added amount of the nanocomposite reinforcing agent Ni-MWCNTs to 0.2 Wt.%, the density was continuously reduced to 95% of the theoretical value of the SAC solder alloy. This was because the compaction resistance of the composite solder powder mixture increased with the increasing content of the Ni-MWCNTs (Ha et al , 2009). Figure 2(b) shows the relationship between the content of Ni-MWCNT reinforcement and the microhardness of the nanocomposite solder.…”
Section: Resultsmentioning
confidence: 99%
“…By increasing the added amount of the nanocomposite reinforcing agent Ni-MWCNTs to 0.2 Wt.%, the density was continuously reduced to 95% of the theoretical value of the SAC solder alloy. This was because the compaction resistance of the composite solder powder mixture increased with the increasing content of the Ni-MWCNTs (Ha et al , 2009). Figure 2(b) shows the relationship between the content of Ni-MWCNT reinforcement and the microhardness of the nanocomposite solder.…”
Section: Resultsmentioning
confidence: 99%
“…However, scale reduction of electronic products increases the current density in solder joints, resulting in enhanced electromigration effects, which can cause reliability problems. [5][6][7][8][9][10] Electromigration refers to the phenomenon of directional atomic movement induced by current stressing, 11,12 which can induce significant microstructural changes, such as void and hillock formation and phase segregation, and affect growth of intermetallic compounds in solder joints. [13][14][15][16][17] To the best of our knowledge, electromigration in Bi-added SnAgCu solder has not been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] As the high current density stressing through the micro solder joints, EMinduced failures seriously threaten the reliability of the flip-chip and 3-D IC package. 5,6,10 Up to now, peoples found that the EM-induced failures typically occurred at the cathode joint interface. The EMinduced cathode metal-pads consumption is one of the major EMinduced failure modes.…”
mentioning
confidence: 99%